CONDITION OF MOUNTAIN ECOSYSTEMS OF THE TIAN-SHAN AND GEO-HAZARDS FORMATION - L E Orolbaeva; A A Meleshko (RUDN Journal of Ecology and Life Safety, 2016)
The article considers the analysis of mountain ecosystems condition of the Tian-Shan affected by antropogenic and climate changes contributing to natural hazards formation. Rugged orography, unstable geodynamic environment of the Tien-Shan, result in the occurrence of such natural processes as landslides, debris flows and floods. The frequency and severity of the natural processes are associated with the condition of forest ecosystems. One of the reasons of mountain ecosystems degradation is deforestation. Moreover, the forest shrinkage in the Inner Tien-Shan defines the mesoclimate and associated glaciation systems of the region.